Categorising Example Sentences in Dictionaries for Research Purposes - Hiles, Lorna (Lexikos, 2011)
Examples in dictionaries come in many different forms. They may be sentences or phrases. They may be corpus-based or made up by the lexicographer. They may contain the lemma in its uninflected form or they may contain an inflection of the lemma. In some dictionaries the function of examples is to provide contextual support to the meaning of the headword, and in others the grammatical support that they provide is more important. While there is literature on the usefulness of examples, and on whether examples should be corpus-based or not, there is very little on what makes one example more useful than another. I have set out to find out what sort of examples South African school users identify as most helpful. In this article, I look at whether examples in five South African school dictionaries do provide suitable contextual or grammatical support. I have constructed a table to classify example sentences according to different criteria. I filled in this table with randomly selected words and their examples which have been taken from five different South African school dictionaries. The goal of this research is to present characteristics of examples in a way that makes them easier to analyse and compare. This should help lexicographers in future dictionaries check whether they have written or selected the best possible examples for their users’ needs.